2019
DOI: 10.4093/dmj.2018.0020
|View full text |Cite
|
Sign up to set email alerts
|

Increased Nociceptive Responses in Streptozotocin-Induced Diabetic Rats and the Related Expression of Spinal NR2B Subunit of N-Methyl-D-Aspartate Receptors

Abstract: Background This study investigated the role of NR2B in a modulated pain process in the painful diabetic neuropathy (PDN) rat using various pain stimuli. Methods Thirty-two Sprague-Dawley male rats were randomly allocated into four groups (n=8): control, diabetes mellitus (DM) rats and diabetic rats treated with ifenprodil at a lower dose (0.5 µg/day) (I 0.5) or higher dose (1.0 µg/day) (I 1.0). DM was induced by a single injection of streptozotocin at 60 mg/kg on day 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…51 The mGlu2-mediated inhibition of glutamate release will restrain the activation of postsynaptic glutamate receptors which are involved in mechanisms of nociceptive sensitization, such as AMPA, NMDA, and mGlu5 receptors. [52][53][54] On the other side of the coin, the glutamate secreted by the cystine/glutamate antiporter might activate extrasynaptic GluN2Bcontaining NMDA receptor and mGlu5 receptors. STZ-induced neuropathic pain is associated with an enhanced phosphorylation of the GluN2B (NR2B) subunit of NMDA receptors and is sensitive to GluN2Bcontaining NMDA receptor blockade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…51 The mGlu2-mediated inhibition of glutamate release will restrain the activation of postsynaptic glutamate receptors which are involved in mechanisms of nociceptive sensitization, such as AMPA, NMDA, and mGlu5 receptors. [52][53][54] On the other side of the coin, the glutamate secreted by the cystine/glutamate antiporter might activate extrasynaptic GluN2Bcontaining NMDA receptor and mGlu5 receptors. STZ-induced neuropathic pain is associated with an enhanced phosphorylation of the GluN2B (NR2B) subunit of NMDA receptors and is sensitive to GluN2Bcontaining NMDA receptor blockade.…”
Section: Discussionmentioning
confidence: 99%
“…STZ-induced neuropathic pain is associated with an enhanced phosphorylation of the GluN2B (NR2B) subunit of NMDA receptors and is sensitive to GluN2B-containing NMDA receptor blockade. 54 In addition, the expression of mGlu5 receptors is increased in the spinal cord of STZ-treated mice as a result of H3 histone acetylation at the Grm5 gene promoter, and activation of the histone deacetylase, sirtuin-1, normalizes the expression of mGlu5 receptors and causes analgesia. 52 To examine whether NAC restrains or facilitates the endogenous activation of NMDA and mGlu5 receptors, we used a cocktail of memantine (a fast NMDA channel blocker 55 ) and MTEP (a negative allosteric modulator of mGlu5 receptors 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…The potential of ifenprodil for the treatment of drug addiction, idiopathic pulmonary fibrosis, and Covid‐19 infections is investigated in clinical trials [ 10–12 ] and, furthermore, its positive effects in animal models of Alzheimer's disease and neuropathic pain have been reported. [ 13–15 ]…”
Section: Introductionmentioning
confidence: 99%
“…Ifenprodil was initially developed as an α 1 receptor antagonist for the treatment of hypertension . Later, it was found that 1 is a potent negative allosteric modulator selectively inhibiting GluN2B subunit-containing NMDA receptors. Commercially available ifenprodil ( unlike racemate, Cerocral®), which is used in Japan as cerebral vasodilator, showed agonistic activity at σ 1 receptors as well. , Clinical trials are currently evaluating the therapeutic potential of 1 for the treatment of drug addiction, idiopathic pulmonary fibrosis (IPF), and COVID-19. Furthermore, 1 showed positive effects in animal models of Alzheimer’s disease and neuropathic pain. However, the selectivity of 1 over other receptors such as σ 1 , σ 2 , α 1 , 5-HT 1A , and 5-HT 2 is rather low and depends on the configuration …”
Section: Introductionmentioning
confidence: 99%